Comparative evaluation of a dentifrice containing calcium sodium phosphosilicate to a dentifrice containing potassium nitrate for dentinal hypersensitivity: A clinical study - Tanya Satyapal; Rohini Mali; Amita Mali; Vishakha Patil (Wolters Kluwer Medknow Publications, 2014)
Background: Calcium sodium phosphosilicate is a recently introduced desensitizing agent which acts by occluding the dentinal tubules and also resists acid decalcification. This study was designed to assess the efficacy of a new toothpaste containing 5% calcium sodium phosphosilicate for the treatment of dentinal hypersensitivity and also compare it with 5% potassium nitrate. Materials and Methods: Sixty patients with the chief complaint of dentinal hypersensitivity were enrolled and randomly divided into two groups. The visual analog scale (VAS) scores were taken for water and air stimuli at baseline, 3 weeks after usage of the respective toothpaste, and 3 weeks after discontinuation of the respective toothpaste. Results: Both the groups showed reduction in hypersensitivity scores at 3 weeks and 6 weeks for air stimulus and cold water. The calcium sodium phosphosilicate group, however, showed significantly reduction in hypersensitivity compared to the potassium nitrate group at any time point for both measures of hypersensitivity. Conclusion: The 5% calcium sodium phosphosilicate group showed immense reduction in dentinal hypersensitivity symptoms. The 5% calcium sodium phosphosilicate showed prolonged effects even after discontinuation as compared to 5% potassium nitrate, due to its dentinal tubular occlusion property.